The Role Of The School Environment On Student Learning Success, A Descriptive Study at MTS Dzunnuraini - Nisa, Ike Hillatun (STAI Asy-Syukriyyah, 2022)
The environment or place where the education process takes place which includes family, school, and community education. Because after all, when talking about educational institutions as a place for education to take place, then of course it will involve environmental issues in which the education is carried out. Everyone who is in the educational institution (family, school and community), will definitely experience changes and developments according to the color and style of the institution. This research aims to explore The environment school. This research uses a qualitative method, namely a Field Reaseach. The results show that the role of the environment is an important foundation in achieving child achievement in MTS schools